Study on the migration law of sulfate in limestone water of typical high ground temperature coal mines - Pinghua Huang; Yuanmeng Li; Zhiheng Yu; Wanyu Peng (Scientific Reports)
Abstract With the trend of deep coal resource extraction becoming normalized, understanding the mechanisms driving sulfate migration and evolution under the coupled effects of high geothermal environments and coal mining is crucial. This study investigates the sources and migration processes of groundwater sulfate under high ground temperature conditions using Self-Organizing Maps, stable isotopes (δ34SSO4, δ18OSO4, δDH2O, δ18OH2O), and Bayesian isotope mixing model (MixSIAR). The results indicate that, influenced by coal mining, the hydraulic connectivity between the aquifers above and below the coal seam is significant. High ground temperature conditions accelerate sulfide oxidation and evaporite dissolution, leading to sulfate concentrations in limestone water that are several times higher than those in normal geothermal coal mines. Additionally, coal mining accelerates groundwater circulation, intensifying mixing processes. The combined application of isotopes (δ18OSO4 and δ34SSO4) and the MixSIAR model reveals that the majority of sulfate in the coal seam’s underlying limestone water originates from evaporite dissolution (39.60%), while the sandstone water is significantly affected by mixing processes, with evaporite dissolution (38.70%) and sulfide oxidation (31.08%) playing equally important roles. These findings provide theoretical support for the utilization and management of groundwater resources in deep coal mines.